Research on combustion and emissions of heavy duty diesel engines under low-speed and low-load conditions in low temperature environments. - Jie Zhang; Gengfei Liu; Huaimin Xu (PLoS ONE)
China has a complex geographical environment, and in order to improve the combustion and emissions performance of heavy-duty diesel engines operating at low temperatures, low-speed and low-load conditions, a cleaner combustion mode has been proposed. This study utilizes a multi-cylinder engine environmental chamber test bench and CONVERGE 3D simulation software to examine the effects of intake temperature, injection timing, and injection pressure on engine combustion and emissions. The results indicate that increasing the intake temperature to 322 K, advancing the injection timing to 1 deg and raising the injection pressure to 120 MPa significantly improved the fuel-air mixture. These adjustments increased the OH radical content, accelerated oxidation cracking rates across low, medium, and high-temperature zones and effectively shortened combustion duration. Consequently, soot emissions were reduced by 23.1%, HC emissions by 33.3%, and CO emissions by 52.3%, demonstrating a significant improvement in combustion efficiency and a reduction in emissions from incomplete combustion.